TUTURAN EKSPRESIF BUNDA CORLA PADA AKUN MEDIA SOSIAL TIKTOK - Inggrid Wulandari; Idawati; Nurhusna (Journal Studies in Indonesian Language and Literature, 2024)
This study aims to: 1) Describe the form of expressive speech meaning contained in Bunda Corla's video on TikTok social media account, 2) Describe the function of expressive speech meaning contained in Bunda Corla's video on TikTok social media account. This type of research is qualitative by using descriptive method. Data collection in December 2023. The instrument in this research is the key instrument. The data collection technique in this study uses the note method and documentation. Data analysis techniques in this research are data reduction, data categorisation and conclusion drawing. The result of this research proves that overall from 11 data, there are 2 data of direct literal speech act form, 2 data of direct non-literal speech act form, and 2 data of indirect literal speech act. The functions of expressive speech acts are the function of praising 2 data, the function of welcoming 1 data, and the function of agreeing 2 data.